Students' Thinking Literacy Process in Mathematical Problem-Solving - Mukhlis Mukhlis; Cholis Sa’dijah; Sudirman Sudirman; Santi Irawati (Postgraduate, University of Mataram, 2024)
This study explores and investigates the process of students’ mathematical thinking literacy in solving mathematical problems. This qualitative descriptive research used a test sheet consisting of one item adapted from the PISA mathematical problem model and interview guidelines, as the instrument. One male and two female participants were selected based on problem-solving characteristics. After that, task-based interviews were carried out to investigate the process of students’ mathematical thinking literacy. Data analysis was initiated by reviewing, reducing, and concluding all collected data to describe students’ mathematical thinking literacy in solving mathematical problems. The findings suggest that mathematical thinking literacy is initiated by understanding the problem (understanding), presenting the problem in a simpler form (specializing) to represent ideas, and creating patterns or relationships (generalizing). Based on the relationship between the problem, the subject predicts a solution (conjecturing) or determines the solution to the problem, re-checks (justifying) the problem-solving process to find a logical final result, and communicates the reasons (convincing) to convince the truth of the results obtained. The results of this study help teachers understand the process of students’ mathematical thinking literacy in solving mathematical problems so that it can be used to determine the appropriate strategy in the learning process to improve students' mathematical problem-solving abilities